2000
DOI: 10.1053/he.2000.6596
|View full text |Cite
|
Sign up to set email alerts
|

production and release of endothelin-1 from the gut and spleen in portal hypertension due to cirrhosis

Abstract: This study was aimed to evaluate the source of endothelin-1 (ET-1) in cirrhotic patients. ET-1 is implicated in the pathogenesis of portal hypertension. However, the mechanism and source for increased plasma ET-1 in cirrhotic patients are still obscure. Plasma ET-1 levels in systemic (SV), superior mesenteric (SMV), and splenic venous (SPV) blood were measured in 23 patients with cirrhosis and 8 controls with normal liver. Fourteen removed spleens were immunohistochemically studied for ET-1, CD34, CD68, and CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 48 publications
0
43
0
2
Order By: Relevance
“…Mouse anti-human TFF2 mAb (GE16C clone; Novocastra Laboratories Ltd., Newcastle, United Kingdom; 1:50 dilution) was used at 4°C for overnight incubation. The streptavidin-biotin peroxidase complex method was used for the immunohistochemical steps and were done with a commercially available kit (Histofine SAB-PO kit; Nichirei, Tokyo, Japan) as we described previously (Nagasue et al, 2000). Color development was done with the peroxidase substrate 3-amino-9-ethylcarbazole.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Mouse anti-human TFF2 mAb (GE16C clone; Novocastra Laboratories Ltd., Newcastle, United Kingdom; 1:50 dilution) was used at 4°C for overnight incubation. The streptavidin-biotin peroxidase complex method was used for the immunohistochemical steps and were done with a commercially available kit (Histofine SAB-PO kit; Nichirei, Tokyo, Japan) as we described previously (Nagasue et al, 2000). Color development was done with the peroxidase substrate 3-amino-9-ethylcarbazole.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…15,16 ET-1 is probably the main factor because of its action at two levels: first, at hepatic stellate cells responsible for intrahepatic resistance to flow as a part of portal hypertension, 17 and second, at a systemic level by increasing systemic vascular resistance. 18 Several studies have shown that patients with cirrhosis have greater ET-1 levels than those with normal hepatic function 7,8,19,20 ; this increase in ET-1 levels correlated with the degree of hepatic dysfunction, portal hypertension, and presence of ascites. Our results also showed a threefold increase in ET-1 levels at the beginning of LT. An inverse correlation of systemic ET-1 levels with portal flow also was shown.…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 levels increase in patients with cirrhosis. [6][7][8] Clinical studies have not elucidated whether ET-1 synthesis during LT occurs mainly in the liver or endothelial cells throughout the vascular systemic bed.…”
mentioning
confidence: 99%
“…3 The streptavidin-biotin peroxidase complex method was employed for the immunohistochemical steps, which were performed with a commercially available kit (Histofine SAB-PO kit; Nichirei, Tokyo, Japan) as described previously. 22 Color development was performed with the peroxidase substrate, 3-amino-9-ethylcarbazole. Positive and negative control slides were always included for each immunostaining procedure.…”
Section: Immunohistochemistry and In Situ Hybridizationmentioning
confidence: 99%
“…Hybridization and the immunohistochemical steps were performed as described previously. 22 A pancreatic tumor specimen, previously known as REG positive, was used as a positive control.…”
Section: Immunohistochemistry and In Situ Hybridizationmentioning
confidence: 99%